ANALISIS POSITIONING PRODUK MJB (MILO JELLY BUBBLE) BERDASARKAN PERSEPSI PELANGGAN (Studi Kasus: Outlet Komplek Tiban Cipta Puri Batam) - Geliga Tieland; Shinta Wahyu Hati (Politeknik Negeri Batam, 2017)
The results of this study indicate that: (1) there is a positive and insignificant relationship with product attribute (X1), proved T-statistic (0.197) smaller than T-table (1.64). (2) there is a positive and significant relationship with product benefit (X2), proved T-statistic (1,768) bigger than T-table (1.64). (3) there is positive and insignificant relationship with product user (X3), proved T-statistic (0,628) smaller than T-table (1.64). (4) there is a positive and significant relationship with competitor (X4), proved T-statistic (1,699) bigger than T-table (1.64). (5) there is a positive and insignificant relationship with product category (X5), proved T-statistic (2.855) smaller than T-table (1.64). (6) there is a positive and insignificant relationship with the price attribute (X6), proved T-statistic (1.996) smaller than T-table (1.64)